Evaluasi Dampak Kebijakan Sistem Penyelenggaraan Pendidikan Inklusif jenjang SMP di Kota Pekalongan - Yosef Hananto; Dyah Lituhayu (Journal of Public Policy and Management Review, 2018)
Inclusion education is an educational service concept that is held for children with special needs with the process of teaching and learning activities in regular schools along with other regular children. The goal is to eliminate discrimination between children with special needs and regular children. In the legislation it is explained that every child who is in the age of study is entitled to get the right to education, including here the child with special needs. The purpose of this research is to see how the learning process that takes place in inclusion school, SMP 10 Kota Pekalongan using 3 main indicators according to Bridgman and Davis are input indicators, process indicators and output indicators. The method used in this research is descriptive qualitative type method using informants from the manager of inclusive education, staff of Education Office of Pekalongan City; the organizers of inclusive education, SMP 10 Kota Pekalongan; the beneficiary (target group) of the parents of the child with special needs. The result of the research shows that in the process of teaching and learning activities that take place in inclusion school, SMP 10 Kota Pekalongan, there are problems related to the absence of modification curriculum, GPK with special education base, at least teachers who have followed technical guidance and upgrading, which is limited and limited by the children with special needs received at the inclusive school of SMP 10 Kota Pekalongan, that is only from one kind of disability that is mentally disabled only. This research will look at the impact of the policy by looking at individual impacts, organizational impacts and impacts on society